2016
DOI: 10.2298/ciceq150430019b
|View full text |Cite
|
Sign up to set email alerts
|

Continuous improvement concepts as a link between quality assurance and implementation of cleaner production: Case study in the generic pharmaceutical industry

Abstract: The subject and the research objective presented in this article is establishing of the relationship between quality assurance and implementation of cleaner production in the generic pharmaceutical industry through the comprehensive concept of continuous improvement. This is mostly related to application of Lean and Six Sigma tools and techniques for process improvement and their link to other known concepts used in the industrial environment, especially manufacturing of generic pharmaceutica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Process, productivity, and product efficiency improvements (energy, water, materials, and use and reuse of productive resources) (Almeida et al, 2015;Altham, 2007;Ashton et al, 2016;Bai et al, 2014Bai et al, , 2015Boltic et al, 2016;Bonilla et al, 2010;Büyükbay et al, 2010;Cabello Eras et al, 2013;Castillo-Vergara et al, 2015;Daylan et al, 2013;Dodić et al, 2010;Dong et al, 2012;Esquer et al, 2016;Mbohwa, 2015, 2010;Geng et al, 2010;Giannetti et al, 2008;Glavič and Lukman, 2007;Hicks and Dietmar, 2007;Huang et al, 2013;Li et al, 2010Li and Hamblin, 2016;Lopes Silva et al, 2013;Malinauskienė et al, 2016;Ochoa George et al, 2010;Oliveira and Alves, 2007;Oliveira Neto et al, 2015;Ozturk et al, 2016;Peng and Liu, 2016;Rahim and Raman, 2015;Ribeiro Massote and Moura Santi, 2013;Rivera et al, 2009;Schaltegger et al, 2012;Severo et al, 2016Severo et al, , 2015Silvestre and Silva Neto, 2014;Thrane et al, 2009;Ulutas et al, 2012;Velazquez et al, 2014;Vieira and Amaral, 2016;Wang et al, 2015;…”
Section: Benefits Arising From the Implementation Of Cleaner Productionmentioning
confidence: 99%
See 3 more Smart Citations
“…Process, productivity, and product efficiency improvements (energy, water, materials, and use and reuse of productive resources) (Almeida et al, 2015;Altham, 2007;Ashton et al, 2016;Bai et al, 2014Bai et al, , 2015Boltic et al, 2016;Bonilla et al, 2010;Büyükbay et al, 2010;Cabello Eras et al, 2013;Castillo-Vergara et al, 2015;Daylan et al, 2013;Dodić et al, 2010;Dong et al, 2012;Esquer et al, 2016;Mbohwa, 2015, 2010;Geng et al, 2010;Giannetti et al, 2008;Glavič and Lukman, 2007;Hicks and Dietmar, 2007;Huang et al, 2013;Li et al, 2010Li and Hamblin, 2016;Lopes Silva et al, 2013;Malinauskienė et al, 2016;Ochoa George et al, 2010;Oliveira and Alves, 2007;Oliveira Neto et al, 2015;Ozturk et al, 2016;Peng and Liu, 2016;Rahim and Raman, 2015;Ribeiro Massote and Moura Santi, 2013;Rivera et al, 2009;Schaltegger et al, 2012;Severo et al, 2016Severo et al, , 2015Silvestre and Silva Neto, 2014;Thrane et al, 2009;Ulutas et al, 2012;Velazquez et al, 2014;Vieira and Amaral, 2016;Wang et al, 2015;…”
Section: Benefits Arising From the Implementation Of Cleaner Productionmentioning
confidence: 99%
“…New business opportunities (market access and (Almeida et al, 2015;Armenti et al, 2011;Boltic et al, 2016;Bonilla et al, 2010;Büyükbay et al, 2010;Castillo-Vergara et al, 2015;Dodić et al, 2010;Mbohwa, 2015, 2010;Giannetti et al, 2008;Hicks and Dietmar, 2007;Huang et al, 2013;Li and Hamblin, 2016;Malinauskienė et al, 2016; 48,15% innovation in sustainable products and processes) Oliveira and Alves, 2007;Oliveira Neto et al, 2015;Ozturk et al, 2016;Ribeiro Massote and Moura Santi, 2013;Severo et al, 2016Severo et al, , 2015Silvestre and Silva Neto, 2014;Thrane et al, 2009;Ulutas et al, 2012;Vieira and Amaral, 2016;Yusup et al, 2015;Zeng et al, 2010) Improvement of the organizational image and strengthening of the relationship with stakeholders (Almeida et al, 2015;Altham, 2007;Büyükbay et al, 2010;Dodić et al, 2010;Fore and Mbohwa, 2010;Hicks and Dietmar, 2007;Li and Hamblin, 2016;Lopes Silva et al, 2013;Oliveira and Alves, 2007;Ortas et al, 2013;Ozturk et al, 2016;Severo et al, 2016Severo et al, , 2015Thrane et al, 2009;…”
Section: Benefits Arising From the Implementation Of Cleaner Productionmentioning
confidence: 99%
See 2 more Smart Citations
“…LSS is a collection of managerial and statistical methods such as Shewhart's control charts, root cause analysis, and value stream mapping that are applied to reduce variability and waste in manufacturing processes . For example, Dassau et al combined LSS with design and control approaches for yield enhancement in biopharmaceutical DS manufacturing, and Boltic et al showed the effectiveness of LSS in improving quality assurance in small‐molecule DS manufacturing . These studies applied well‐known industrial approaches for process performance improvement, but lacked a rigorous description of the complex pharmaceutical environment in which these processes occurred.…”
Section: Introductionmentioning
confidence: 99%